DACA, mobility investments, and economic outcomes of immigrants and natives - Jimena Villanueva Kiser; Riley Wilson (W.E. Upjohn Institute for Employment Research, 2024)
Exploiting variation created by Deferred Action for Childhood Arrivals (DACA), we document the effects of immigrant legalization on immigrant mobility investments and economic outcomes. We provide new evidence that DACA increased both geographic and job mobility of young immigrants, often leading them to high-paying labor markets and licensed occupations. We then examine whether these gains to immigrants spill over and affect labor market outcomes of U.S.-born workers. Exploiting immigrant enclaves and source-country flows of DACA-eligible immigrants to isolate plausibly exogenous variation in the concentration of DACA recipients, we show that in labor markets where more of the working-age population can access legal protection through DACA, U.S.-born workers see little-to-no change in employment rates and actually observe increases in wage earnings after DACA's implementation. These gains are concentrated among older and more educated workers, suggesting immigrant workers complement U.S.-born workers and immigrant legalization generates broader local labor market benefits.
Keywords: J15; K37; R23; 330; Legal states; DACA; immigration; geographic mobility; job mobility; occupational licensing; local labor markets